Leisure or Free Time? The Experiences of Elderly People in Social Care Institutions - Charenkova, Jūratė (Socialinė teorija, empirija, politika ir praktika, 2017)
The amount of free time in older age significantly increases because of retirement. This period of life can be used for a beloved activity, be a source of self-development, a chance for new experience, rest, joy or even finance. On other hand, an increased amount of free time can cause issues and negative experiences like boredom, vacuity and the absence of something meaning in one’s actions. Engaging in personally meaningful leisure activities is characterized as one of the most effective ways to cope with changes in older age and also one of the key elements to successful aging.6 elderly people and 3 social workers of Vilnius social care institutions for elderly care participated in qualitative research. Ideas of social contructivism and the identity theories of Giddens (2000) were used for the analysis of data. Data of research showed that the understanding of leisure and the experience of it differentiates depending on individual possibilities to participate in personally meaningful leisure activities. A continuity of leisure activities helps in preserving a feeling of identity continuation; therefore, it is important to secure possibilities for elderly people to participate in leisure activities that were important to them in their adulthood.
Keywords: organization of leisure; personally meaningful leisure activities; elderly people; social care institutions; self-identity